The coupled occurrence of Cimmeriella-Jakutoproductus (Brachiopoda: Productidina) in Patagonia: implications for Early Permian high to middle paleolatitudinal correlations and paleoclimatic reconstruction - Taboada, Arturo Cesar (2010)
The brachiopod species Jakutoproductus sabattiniae sp. nov. and Cimmeriella willi sp. nov. from the Cisuralian deposits of the Tepuel-Genoa basin are described here. Biostratigraphy and stratigraphy of the uppermost section of the Tepuel Group (Mojón de Hierro and Río Genoa formations) are analyzed and a distinctive faunal succession is recognized: the Cimmeriella and Jakutoproductus faunal assemblages of late Sakmarian (Sterlitamakian) and early Artinskian estimated ages, respectively. The lower Permian correlations of these faunal occurrences and the chronology of mostly early Permian glacial episodes between Western and Eastern Argentina with Patagonia are discussed. The coupled Verchojania-Jakutoproductus, Eurydesma-Cimmeriella and Cimmeriella-Jakutoproductus faunal records have been used as a tool for the correlation of early Permian marine sequences from the high to middle paleolatidudinal settings of both hemispheres.